Hubungan Antara Kecerdasan Emosi dan Masa Verja dengan Penjualan Adaptif - Ema Yudiani (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2005)
Insurance agents as the marketers in the insurance business are the front liners for the success of the company, therefore their service qualities need to be improved. One of the service qualities which needs an improvement is their adaptive selling. Adaptive selling is a selling way used by an insurance agent in such a way that He/She should adapt himself/herself to their prospective customers needs and characteristics. The adaptive selling is important to improve since those insurance agents especially in Indonesia are still using, say the ordinary way, the same technique and the same approach to different persons. The adaptive selling will be in relevant to emotional intelligent and length of stay, in which these two variables will affect the improvement of adaptive selling to insurance agents. This research aimed to examine the correlation between emotional intelligence and length of work with adaptive selling of Bumiputera 1912 life insurance agents in Palembang branch offices. This research employeed a purposive sampling method. The subjects of this research were 154 agents of life insurance. The data were collected by the means of two questionnaires: the adaptive selling questionnaire and the emotional intelligence quietionnaire. Data were analyned using multiple regression and product moment correlation analysis. The result of this research are: (1) there was a very significant correlation between emotional intelligence with adaptive selling of life insurance agents, and (2) there was not significant correlation between length of work with adaptive selling of life insurance agents.Key words: adaptive selling, emotional intelligence, life insurance agents.